Dual neutralisation of IL-17F and IL-17A with bimekizumab blocks inflammation-driven osteogenic differentiation of human periosteal cells. Issue 2 (28th July 2020) - Shah, Mittal; Maroof, Asher; Gikas, Panos; Mittal, Gayatri; Keen, Richard; Baeten, Dominique; Shaw, Stevan; Roberts, Scott J
Abstract : Objectives: Interleukin (IL)-17 signalling has been shown to be a key regulator of disease in ankylosing spondylitis (AS) with several IL-17 blockers currently clinically approved. Despite this, the role of IL-17 in bone pathology is poorly understood. This study aimed to investigate IL-17 signalling in the context of pathological bone formation. Methods: A biomimetic human periosteum-derived cell (hPDC) model of osteogenic differentiation was used in combination with recombinant IL-17 cytokines, T-cell supernatants or serum from patients with AS. IL-17A, IL-17F and bimekizumab monoclonal antibodies were used to block IL-17 cytokine action. Results: Recombinant IL-17A and IL-17F are pro-osteogenic with respect to hPDC differentiation. T helper 17 or γδ-T cell supernatants also potently stimulated in vitro bone formation, which was blocked deeper by dual inhibition of IL-17A and IL-17F than by neutralisation of IL-17A or IL-17F individually. Osteogenic blockade may be due to an increase in expression of the Wnt antagonist DKK1 . Interestingly, osteocommitment was also induced by serum obtained from patients with AS, which was also abrogated by dual neutralisation of IL-17A and IL-17F. Conclusions: These data show for the first time that IL-17A and IL-17F enhance in vitro osteogenic differentiation and bone formation from hPDCs, inhibition of which may offer an attractive therapeutic strategy to prevent pathological bone formation.